Comparative Analysis of Community Trust in Policing Strategies Under Martial Law in Latvia, Lithuania, and Ukraine - Dzikas, Darius (Український політико-правовий дискурс, 2025)
The study is devoted to a comparative analysis of the level of public trust in the police under martial law in Ukraine, Latvia and Lithuania. In times of crisis, especially in times of war, law enforcement agencies perform not only the function of a security guarantor but also play a key role in shaping the relationship between the state and society. The purpose of the study is to identify the factors that influence the level of trust in law enforcement agencies in wartime and compare the strategies and approaches used in the analysed countries to strengthen it. Particular attention is paid to assessing the effectiveness of police reforms, the transparency of their activities and the level of interaction with citizens in wartime. A set of methodological approaches was used to achieve this goal, including analysis of regulatory documents, comparative studies of political and legal systems, and sociological surveys that reflect public opinion on police strategies and methods in wartime. The comparative analysis of Ukraine, Latvia, and Lithuania allows us to assess not only the effectiveness of different approaches to public security but also to identify universal trends that can be adapted to increase the level of trust in the police in each country studied. The study results show that the level of trust in the police in Ukraine, Latvia and Lithuania largely depends on the historical context, social and psychological climate and the effectiveness of the reforms. In Ukraine, trust in law enforcement agencies in wartime is declining due to several factors, including shortcomings in police performance, lack of transparency in its work, and poor interaction with citizens. At the same time, the situation in Latvia and Lithuania is more stable due to more effective approaches to law enforcement management and active integration of the police into civic initiatives. Despite the differences in strategies, all three countries face common challenges related to using modern technologies to increase law enforcement transparency and strengthen public control. The study’s findings confirm the need to focus on increasing the transparency of law enforcement agencies, enhancing police cooperation with the public, and improving reforms aimed at strengthening the effectiveness of law enforcement. Key recommendations include introducing digital technologies to enhance public oversight, developing effective communication strategies between the police and the public, and ensuring the stable functioning of mechanisms for public oversight of law enforcement during the war.